EFFECT OF MUSA BALBISIANA COLLA EXTRACT ON BREAST MILK PRODUCTION IN BREASTFEEDING MOTHERS - Diyan Wahyuningsih; Syarief Taufik Hidayat; Nur Khafidhoh; Ari Suwondo; Diyah Fatmasari; Kun Aristiati Susiloretni (Belitung Nursing Journal, 2017)
Background: Musa balbisiana Colla, known as Jantung Pisang Klutuk or Pisang Batu, is considered as a traditional food that can increase breast milk production. Little is known about its benefit in Indonesia. Thus, to examine the impact of Musa balbisiana Colla on the production of breast milk is needed. Objective: This study aims to examine the effect of the extract of banana flower (Musa balbisiana Colla) to increase milk production of breastfeeding mothers. Methods: This was a quasi-experimental study with pretest-posttest control group design. This study was conducted in the working area of the Health Center (Puskesmas) of Pesantren II in January – February 2017. There were 16 respondents were selected by accidental sampling, divided into intervention group (8 respondents) and control group (8 respondents). Randomization was performed to select the respondent in each group. The quantity of milk production was measured based on the volume of milk production, while the quality of milk production was based on the levels of prolactin in early (pre) and late (post) using Electro Chemi-Luminescence Immunoassay (ECLIA) method. Independent t-test was used to analyze the data. Results: Findings showed that the mean of the volume of the breast milk production in the experiment group was 470.681 ml and in the control group was 364.650 ml with SD 113.502. The mean of prolactin levels in the experiment group was 35.337 nanogram and in the control group was -38.381 nanogram. There was a significant effect of consuming Musa balbisiana Colla extract on the volume of breast milk production (p-value 0.003) and prolactin levels (p-value 0.001) (<0.05). Conclusion: There was a significant effect of banana flower (Musa balbisiana Colla) extract on breast milk production and prolactin level in breastfeeding mothers. The findings of this study could be used to be alternative daily menu for postpartum mothers and a solution for midwives to deal with those who have inadequate production of breast milk and low prolactin levels.